Investigation of glass plate failure mechanism subjected to copper and steel projectile impacts - Shah, Qasim Hussain; Aung, Kya Myo (IIUM Press, 2014)
A glass plate was subjected to impact by spherical copper and steel projectiles at low velocities. The glass failure features consisted of a central Hertzian cone made up of comminuted glass and a spider web like cracking pattern around the cone with circumferential and radial cracks. The objective of the investigation was to determine if the damage caused by copper projectile impact compared to steel projectile impact was higher for the same kinetic energy (K.E.) projectiles and the reason for this phenomenon. For the constant K.E. impact, copper projectile apparently caused higher damage in glass plate. Higher damage was attributed to projectile contact duration and the contact area between the projectile and the glass plate. Finite element analysis using LS-DYNA based upon maximum principal strain failure criterion for laminated glass model was able to predict the failed material under the impact location and the cracking pattern in the glass plate for a biased meshing scheme. Radial cracks in glass target were reported to be 15% higher for copper projectile impact than the steel projectile impact.